WCIP method for multiple‐loop antennas around a spherical media. Issue 5 (28th February 2019) - Ammar, Noemen; Baudrand, Henri
Abstract : In this study, the wave concept iterative process method is developed in a spherical coordinate system in order to investigate the characteristic of multiple‐loop antennas around a multilayer sphere. The analysis method is based on the incoming and outgoing waves defined from the tangential electromagnetic fields at the interfaces of the layers. The iterative process is governed by two systems of equations linking the waves in spectral and spatial domains. The toggling between the two domains is insured by the Legendre transformation. Numerical results consider single and multiple loops (both activated and parasitic loops) around a metallic sphere coated by one or several dielectric layers. The mutual coupling and the radiation characteristic of a loop excited by two feeding sources are analysed. The influence of parasitic loops on the return loss of the activated loop is extensively investigated including the number and the position of the loops on the sphere. The coupling sensitivity between two activated feeding sources is also investigated. The presented results agree very well with the simulation and the literature.